DIGITALISASI SISTEM INFORMASI AKUNTANSI UMKM: ANALISIS KUALITATIF BERBASIS TOE DAN RBV - Arif Hasdik; Nurkholifah Burhanuddin; Desi Ratna Dewi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the digitalization of Accounting Information Systems (AIS) in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through an integrated Technology-Organization-Environment (TOE) and Resource-Based View (RBV) approach, as well as to identify the factors influencing technology adoption and implementation success. The research employed a descriptive qualitative method using secondary data collected from government reports, statistical databases, national and international scientific journals, and industry reports related to MSME digitalization during the 2016–2026 period. Data were analyzed through documentation studies using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, supported by coding techniques and source triangulation. The findings reveal that technological, organizational, and environmental factors play significant roles in encouraging the adoption of digital AIS, while internal organizational capabilities, including digital literacy and human resource competencies, determine implementation success. Digital AIS has been shown to improve operational efficiency, data accuracy, and decision-making quality among MSMEs, although challenges such as low digital literacy, limited infrastructure, and financial constraints remain. The study concludes that the success of AIS digitalization in MSMEs is determined not only by technology adoption but also by the readiness of internal resources to utilize technology effectively and sustainably, thereby creating strategic value and enhancing business competitiveness. Keywords: Accounting Information Systems, Digitalization